2022
DOI: 10.1002/ece3.9313
|View full text |Cite
|
Sign up to set email alerts
|

Decision support for aquatic restoration based on species‐specific responses to disturbance

Abstract: Disturbances to aquatic habitats are not uniformly distributed within the Great Lakes and acute effects can be strongest in nearshore areas where both landscape and within lake effects can have strong influence. Furthermore, different fish species respond to disturbances in different ways. A means to identify and evaluate locations and extent of disturbances that affect fish is needed throughout the Great Lakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…Overlay of those data on the study area provided an association of disturbance conditions with observed fish assemblages. However, cause and effect were not established here, and different species respond in different ways to environmental disturbances; some may thrive at high disturbance, while others are intolerant of even little disturbance (McKenna et al 2022). Mooneye, especially the population trapped between dams in the Oswegatchie River, may be most sensitive.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Overlay of those data on the study area provided an association of disturbance conditions with observed fish assemblages. However, cause and effect were not established here, and different species respond in different ways to environmental disturbances; some may thrive at high disturbance, while others are intolerant of even little disturbance (McKenna et al 2022). Mooneye, especially the population trapped between dams in the Oswegatchie River, may be most sensitive.…”
Section: Discussionmentioning
confidence: 96%
“…Several of our T&E species occupy habitat in those areas, and although these species are considered intolerant of disturbance (Halliwell et al 1999), their highest abundances were associated with moderate disturbance values. Responses of fish abundances to disturbance vary widely by species, with some being intolerant of very low disturbance levels, but many thriving at higher levels (McKenna et al 2022). The association of Lake Sturgeon and Eastern Sand Darter with a wide range of disturbance conditions may reflect those preferences or could indicate that a critical disturbance factor is missing from the index for these species.…”
Section: Potential Threats To Threatened and Endangered Speciesmentioning
confidence: 99%
“…2015; McKenna et al. 2022). Habitat conditions are likely key to recovery, and both the natural ability of some habitats to support Silver Chub and the extent of anthropogenic disturbance differ throughout this species' range (Kinney 1954; Dunn et al.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study identified multimetric disturbance gradients to which Great Lakes fish abundances respond (McKenna et al. 2022). That work filtered out the effects of natural environmental conditions to develop species‐specific models of fish abundance in response to anthropogenic disturbances throughout the Great Lakes, including models for Silver Chub.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation